De-agrarization of rural female employment and working hours in Peru - Loayza Alatrista, Sulema (2020)
Rural employment in the country is facing in recent years structural changes that have to do with the process of de-agrarization of the fi land, in the context of globalization and market economy penetration, in a world that registers an increasing demand for food. The occupational de-agrarization of rural areas in Peru registers a significant participation of women in non-agricultural remunerated tasks, in the growing agroindustrial activity located mainly in the coastal valleys. In this article we seek to identify the processes and ways in which the non-agrarian occupational diversification of rural women in the Motupe-Lambayeque valley has taken place, establishing the socio-cultural and economic conditions that drive women to sell their labor to non-agrarian production activities, facing challenges that have to do with socio-cultural restrictions on their productive capacity and economic and social recognition; in addition to the complexity of the network of working hours and household chores.